2001
DOI: 10.1002/app.1172
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of silk fibroin/chitosan blend films

Abstract: Silk fibroin/chitosan blend films were examined through IR spectroscopy to determine the conformational changes of silk fibroin. The effects of the fibroin/chitosan blend ratios (chitosan content) on the physical and mechanical properties were investigated to discover the feasibility of using these films as biomedical materials such as artificial skin and wound dressing. The mechanical properties of the blend films containing 10 -40% chitosan were found to be excellent. The tensile strength, breaking elongatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
161
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(167 citation statements)
references
References 22 publications
5
161
0
1
Order By: Relevance
“…The absorption bands of SF are assigned as follows; the bands at 1660 (amide I), 1540(amide II), and 1235 cm -1 (amide III) were assigned to the random coil structure, the bands at 1630 (amide I), 1530(amide II), and 1265 cm -1 (amide III) â-sheet conformation. (Kweon et al, 2001, Tsukada et al, 1994Magoahi et al, 1985. Fig.…”
Section: 4% 60mentioning
confidence: 99%
See 1 more Smart Citation
“…The absorption bands of SF are assigned as follows; the bands at 1660 (amide I), 1540(amide II), and 1235 cm -1 (amide III) were assigned to the random coil structure, the bands at 1630 (amide I), 1530(amide II), and 1265 cm -1 (amide III) â-sheet conformation. (Kweon et al, 2001, Tsukada et al, 1994Magoahi et al, 1985. Fig.…”
Section: 4% 60mentioning
confidence: 99%
“…SF has good mechanical and biological properties including low inflammatory reaction (Santin et al, 1999), good water vapor and oxygen permeability (Kweon et al, 2001;Minoura et al, 1990), blood compatibility (Sakabe et al, 1989), alkaline phosphatase activation (Kim et al, 2010a), and acceleration of collagen formation, and proliferation of cultured human skin fibroblasts (Yeo et al, 2000;Yamada et al, 2004). Therefore, SF has been attempted in wide varieties of biomedical applications such as matrix for mammalian cell culture and enzyme immobilization (Minoura et al, 1995), scaffold for bone substitution (Sofia et al, 2001), wound dressing (Kweon et al, 2008), and drug delivery carrier (Hanawa et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the resistance of membranes presented higher value than pure polymers, due to the increase in β-sheet conformational transition [9]. Kweon et al (2001) studied films of SF and CHI to understand the effect of fibroin and chitosan ratio on the physical characteristics of blends. They verified that the mechanical properties the films were improved when blends were formed with 10-40% chitosan [10].…”
Section: Introductionmentioning
confidence: 99%
“…Kweon et al (2001) studied films of SF and CHI to understand the effect of fibroin and chitosan ratio on the physical characteristics of blends. They verified that the mechanical properties the films were improved when blends were formed with 10-40% chitosan [10]. Lee et al (2004) studied the physical and structural properties of SF and sodium alginate blends and concluded that the structural characteristics of SF in blends were not affected by the incorporation of sodium alginate.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, silkworm cocoon has been used to make a textile fiber and surgical suture for several thousand years. Recently useful biological properties of silk protein have been reported by researchers; acceleration of collagen formation, and proliferation of cultured human skin fibroblasts (Yeo et al, 2000;Yamada et al, 2004), matrix for mammalian cell culture and enzyme immobilization (Minoura et al, 1995), scaffold for bone substitution (Sofia et al, 2001), and drug delivery carrier (Hanawa et al, 1995), oxygen and water vapor permeability Minoura et al, 1990;Kweon et al, 2001, and blood compatibility (Sakabe et al, 1989).…”
Section: Introductionmentioning
confidence: 99%